Formulation of Dihydroartemisinin-Piperaquine (DHP) Generic Tablet as Antimalarials Drug - Yunarto, Nanang; Isnawati, Ani; Aini, Nurul; Kurniatri, Arifayu Addiena; Adelina, Rosa; Setyorini, Herni Asih (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
The incidence of malaria in Indonesia is about two million cases annually. Dihydroartemisinin-piperaquine (DHP) is the first line therapy recommended for uncomplicated malaria treatment, whereas DHP is still fully imported. The generic DHP tablet formulation has the potential to become the first of DHP drug which is locally produced. This study is aimed to formulate generic DHP film coated tablets for antimalaria drug. Tablets were compressed with the combination of wet granulation for piperaquine phosphate (PQP) and direct compression method for DHA and coated with a moisture barier coating material. The parameters to evaluate the quality of DHP tablets are physical properties, assay, and dissolution test. DHA and PQP assay were performed by HPLC method. The dissolution testing was conducted by in house method using HCl 0.1 N medium. The result shows physical properties of filmcoated tablets meet the requirement, i.e. uniform weight, 7.0-8.5 kp hardness, 0.02% friability and 3 minute 22 seconds disintegration. The assay to determine DHA in tablet was 95.17% and PQP was 97.05%. The result of dissolution testing shows the content of DHA and PQP in the tablet were 113.51% and 96.55%, respesctively. The formulation which is developed meets the general requirement of API in tablet 90–110% and dissolution requirement >75%.